PERSEPSI MASYARAKAT TENTANG INFRASTRUKTUR PEMBANGUNAN DI KECAMATAN V KOTO KABUPATEN MUKOMUKO - Mursil, Mursil; Rianto, Slamet; U, Iswandi (STKIP PGRI Sumbar, 2013)
This study aims to determine the public perception about the development of infrastructure in V Koto Mukomuko districts which include: 1) infrastructure Â of road, 2) infrastructure of educational, 3) infrastructure of hospital, 4) infrastructure of office, and 5) infrastructure of tourism.This research is descriptive. Population in this research is all the people in the district V Koto district , amounting to 1,613 households Mukomuko . Samples were taken with a proportional random sampling technique with the proportion of 10%, so that the population of 163 families.The research found that : 1 ) Perception of road infrastructure masyaraka the mean is 3,35 with 66,97 % of respondents the level of achievement that is in pretty good criteria , 2 ) Community perceptions of educational infrastructure with the average score was 3,39 the achievement level of 67,73 % of respondents who are in pretty good criteria, 3 ) community perceptions of hospital infrastructure mean score was 3,56 with 71,15 % respondents level of achievement on the criteria that are good enough , 4 ) Perception of about the office infrastructure is the average score of 2,93 with 58,53 % of respondents level of achievement on the criteria that are poor and 5) community perceptions of tourism infrastructure mean score was 3,65 with 72,94 % of respondents rate the performance are in fairly good criterion